Insights into the phylogenetic diversity, biological activities, and biosynthetic potential of mangrove rhizosphere Actinobacteria from Hainan Island - Ye, Jing-jing; Zou, Ren-jian; Zhou, Dong-dong; Deng, Xiao-lin; Wu, Ni-lin; Chen, Dan-dan; Xu, Jing (Frontiers in Microbiology, 2023)
Mangrove rhizosphere soils host diverse Actinobacteria tolerant to numerous stresses and are inevitably capable of exhibiting excellent biological activity by producing impressive numbers of bioactive natural products, including those with potential medicinal applications. In this study, an integrated strategy of combining phylogenetic diversity, biological activities and biosynthetic gene clusters (BGCs) screening approach were applied to investigate the biotechnological importance of Actinobacteria isolated from mangrove rhizosphere soils from Hainan Island. The actinobacterial isolates were identified using a combination of colony morphological characteristics and 16S rRNA gene sequences analysis. A total of 287 actinobacterial isolates affiliated to 10 genera in 8 families of 6 orders were isolated from 5 different mangrove rhizosphere soil samples, specifically, Streptomyces (68.29%) and Micromonospora (16.03%), of which 87 representative strains were selected for phylogenetic analysis. The crude extracts of the 39 isolates (44.83%) showed antimicrobial activity against at least one of the 6 tested indicator pathogens, especially ethyl acetate extracts of A-30 (Streptomyces parvulus), which could inhibit the growth of 6 microbes with minimum inhibitory concentration (MIC) values reaching 7.8 µg/mL against Staphylococcus aureus and its resistant strain, comparative to clinical antibiotic ciprofloxacin. Furthermore, 79 crude extracts (90.80%) and 48 (55.17%) of the isolates displayed anticancer and immunosuppressive activities, respectively. Besides, 4 rare strains exhibited potent immunosuppressive activity against the proliferation of Con A-induced T murine splenic lymphocyte in vitro with inhibition rate over 60% at 10 μg/mL. Based on the results of PCR-detected BGCs screening, type I and II polyketide synthase (PKS) and non-ribosomal synthetase (NRPS) genes, were detected in 49.43%, 66.67%, and 88.51% of the 87 Actinobacteria, respectively. To highlight, these strains (26 isolates, 29.89%) harbored PKS I, PKS II and NRPS genes in their genomes, nevertheless their bioactivity is independent of BGCs in this study. Our findings highlighted antimicrobial, immunosuppressive and anticancer potential of mangrove rhizosphere Actinobacteria from the Hainan Island and the biosynthetic prospecting of exploiting the corresponding bioactive natural product.